Return to Sport After Arthroscopic Rotator Cuff Repair in Middle-Aged and Elderly Swimmers - Shimada, Yohei (Orthop J Sports Med, 2020)
BACKGROUND: No reports have been published on the clinical outcomes, including return to sport, after rotator cuff repair in middle-aged and elderly swimmers with rotator cuff tears. PURPOSE: To retrospectively investigate clinical outcomes and return to sport after arthroscopic rotator cuff repair in middle-aged and elderly swimmers. STUDY DESIGN: Case series; Level of evidence, 4. METHODS: Patients who underwent arthroscopic rotator cuff repair and met the following criteria were included: (1) age older than 45 years, (2) rotator cuff tears confirmed during surgery, (3) arthroscopic suture bridge rotator cuff repair, (4) primary surgery, and (5) swam more than once a week before surgery. The exclusion criteria were as follows: (1) irreparable large and massive tears, (2) shoulder instability, (3) arthritis or rheumatic disorders, or (4) less than 2-year follow-up. We investigated functional outcomes including range of motion; the University of California, Los Angeles (UCLA) score; the American Shoulder and Elbow Surgeons (ASES) score; return to swimming; and the return rates for each style of swimming. In addition, the functional outcomes and findings of magnetic resonance imaging were compared between the group with complete return and the group with incomplete or failed return. RESULTS: A total of 32 shoulders in 31 middle-aged and elderly swimmers (5 males, 26 females) were included. The mean age was 65 years (range, 47-78 years), and the mean follow-up was 47 months (range, 24-86 months). Return to swimming was achieved in 31 (97%) shoulders at a mean of 8 months (range, 3-24 months), and complete return was achieved in 18 (56%) shoulders at a mean of 12 months (range, 3-24 months). The return rate was 97% for freestyle, 83% for breaststroke, 74% for backstroke, and 44% for butterfly stroke. Postoperative UCLA and ASES scores were significantly higher in the group with complete return than in the group with incomplete or failed return (P = .001 and .01, respectively). Postoperative forward elevation was significantly better in the complete return group (P = .01). CONCLUSION: This study demonstrated that 97% of elderly swimmers who underwent arthroscopic rotator cuff repair could return to swimming. The complete return rate was 56%; however, the group with incomplete or failed return showed poorer active forward elevation. Freestyle had the highest complete return rate, whereas the butterfly stroke had the lowest return rate. It may be important to achieve good active forward elevation postoperatively to return to swimming.